Um estudo sobre mediações de conflitos, relações de poder e justiça na escola - Antonio, Patricia De Oliveira [UNIFESP] (2019)
This research explored the manifestations of people involved in conflict situations at school with the intent of recognizing the aspects of culture associated with the relations of teachings about power and justice. The research was conducted at a Guarulhos public school between the 1st and 3rd grades of Elementary School. The following techniques were applied for data collection: (1) analysis of documented records that the school made regarding conflicts that occured between the 1st and 3rd grades of Elementary School; (2) observation of the school’s routine; (3) interviews with people envolved in the mediation and resolution of conflicts; (4) follow up on the implementarion of a disciplinary project in some classes. Altogether, 12 people were interviewed: (1) three 3rd grade students involved in constant conflicts; (2) two mothers of students considered victims in conflicts that were observed and mediated; (3) three theachers, of which two developed the diciplinary project in 1st and 2nd grade classes and one that showed different practices from rest of the team in her 1st grade class; (4) an academic coordinator of the school that mediated a conflict between two students and was also, in part, responsible for the elaboration and implementation of the disciplinary project; (5) two academic agents responsible for children out of the classroom; and (6) a pedagogical trainee that accompanies handicapped children that are included in the 1st grade in which the disciplinary project was developed. The main theoretical basis of study for the discussed issues, such as power relations and symbolic violence, was based on the work of Pierre Bourdieu, and for the reflexion about justice in school, the work of François Dubet along with experts that dialogue with these authors, such as Flavia Schilling were used. The culture in school was analysed according to Antonio Viñao Frago e Dominique Juliá. Júlio Groppa Aquino was the author used for the discussion about conflict, indiscipline and violence. Among the research results, it is highlighted that the expectation regarding students behavior can somethimes superimpose academic expectations. Although some students completed all academic activies proposed by the teacher, including homework, they were placed in and underprivileged position because they hadn´t shown a passive and appropriate behavior according to the obligations of the school culture. The initial hypothesis was that the representation of subjects would reveal the school´s cultural aspects about hierarchical power relations and the practices impregnated with the moralizing and the civilizing intentions that were focused on adults and punishment. Although the hypothesis was confirmed, throughout the research development, it was also possible to identify that the living and complex reality of daily school routine is tensioned by the contradictions and the resistances that can be favorable ways to build a fairer and more democratic school environment that produces a culture of respect and promotes human rights.